Systematic Literature Review: Pengembangan E-LKPD pada Pembelajaran Matematika - Nurhasanah, Heni; Meiliasari (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The development of E-LKPD (Electronic Student Worksheets) in mathematics education represents an effort to integrate learning strategies with information technology. This study employs the Systematic Literature Review (SLR) method, aiming to identify, evaluate, and interpret various research findings related to E-LKPD over the past five years (2021-2025). The focus of the study encompasses the components of E-LKPD, challenges in its development and implementation, as well as the effectiveness of E-LKPD on students' mathematical abilities. An analysis of 20 articles revealed that the primary components of E-LKPD include covers, lesson identity, usage instructions, learning objectives, material presentation, exercise problems, and evaluation. Common challenges encountered include a lack of digital facilities such as smartphones or PCs, the readiness of teachers and students to utilize digital tools, and suboptimal digital platforms. The effectiveness of E-LKPD has been shown to enhance mathematical skills, including numeracy, creative thinking, critical thinking, problem-solving, metacognition, self-directed learning, and self-efficacy. The findings of this research aim to encourage educators to develop more effective E-LKPD, thereby positively impacting students' mathematics learning outcomes.